Coping strategies employed by older Nepalese migrant women to manage their mental distress in the UK: A qualitative research. - Lalita Kumari Sah; Rajeeb Kumar Sah; Devendra Raj Singh; Rochelle A Burgess (PLoS ONE)
Introduction Mental health and wellbeing is a global public health concern. However, there is limited evidence on managing the mental health needs of the Nepalese migrant population in the UK. This paper is focused on exploring coping strategies employed by older Nepalese migrant women in managing their mental distress. Methods A qualitative study informed by a narrative approach was conducted among twenty Nepalese older women living in London. Interviews were analysed using thematic analysis. Results Findings identified three major coping strategies used by Nepalese older women: i) Engaging others to access human, social and economic resources in problem focussed strategies; ii) Using emotion-focussed strategies through drawing on human and social resources; and iii) Employing emotion-focussed strategies through prayer and acceptance. Each strategy reflected the strategic use of existing resources, highlighting a strong sense of ownership over their mental wellbeing. Conclusion Nepalese women used both problem-focused and emotion-focused coping strategies to manage their mental distress while living in the UK. However, they had poor awareness of the availability or potential benefits of mental health services in managing their distress and were not able to identify their everyday survival as strengths. We assert social interventions that build on women's abilities are essential to promote mental health and wellbeing.